Implementing proactive gender pay equity legislation : a study of Icelandic and Canadian pay equity legislation and its future impacts on the gender wage gap - Monique Delorme 1990- (2019)
This study will be looking into the primary factors that influence the implementation of gender pay equity legislation. The central focus will be on Icelandic companies, however to understand the universality of these implementation factors, strategies, and barriers, Canadian insights will also be included in the analysis. The key elements investigated in this study include, organizational gender demographics, implementation strategies, implementation barrier, key success factors, and potential long-term implications of gender pay equity legislation. The purpose of this study is to examine how organizations are applying gender pay equity legislation, and whether or not this legislation will successfully address the factors contributing to the gender wage gap. The findings of this study suggest that occupational gender segregation continues to play a large part in the gender wage gap. It was also found that there are similar techniques being used to implement gender equity legislation in both Iceland and Canada. In particular, having well-structured documentation and the use of outside consultants have been identified as important factors in the implementation process. In terms of barriers and challenges, Iceland presented with fewer internal barriers than Canada, partly due to higher levels of internal support and stricter legislative enforcement. The current legislative movement towards achieving equitable compensation for women and men in Iceland is a positive change, however, it is too soon to tell if it will be effective enough to eliminate the wage gap. The dominant sentiment amongst participant was that through the new legislation is a step in the right direction, it will not have a major impact on their businesses or industry as a whole. It was concluded that larger societal changes are needed to correct the underlying causes of wage discrepancies.